2015
DOI: 10.1016/j.carbon.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and face dependent copper–graphene interactions

Abstract: A B S T R A C TThe interaction between graphene and metals represents an important issue for the largearea preparation of graphene, graphene transfer and the contact quality in graphene devices. We demonstrate a simple method for estimating and manipulating the level of interaction between graphene and copper single crystals through heat treatment, at temperatures from 298 K to 1073 K. We performed in-situ Raman spectroscopy showing Cu face-specific behavior of the overlying graphene during the heat treatment.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 43 publications
(108 reference statements)
1
15
0
Order By: Relevance
“…compare figures 2(a)-(c)). This finding is consistent with the aforementioned studies that found that (001) produced the weakest Cu-G bonding in both polycrystalline [31] and monocrystalline [32] samples. [42].…”
Section: Transmission Electron Microscopysupporting
confidence: 93%
See 1 more Smart Citation
“…compare figures 2(a)-(c)). This finding is consistent with the aforementioned studies that found that (001) produced the weakest Cu-G bonding in both polycrystalline [31] and monocrystalline [32] samples. [42].…”
Section: Transmission Electron Microscopysupporting
confidence: 93%
“…For a polycrystalline Cu substrate, the (111) grains produced the highest-quality graphene, especially better than the (001) grains [31]. Similarly, single-crystal Cu substrates in the (111) orientation more strongly bonded to graphene than substrates in (001) and (011) orientations [32]. Other than type and orientation, perhaps the most important feature of the substrate is its susceptibility to oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…[34] It was shown previously that, for graphene grown on single crystals of copper, the graphene-substrate interactions strongly depended on the face of the coppers urface. [38,39] This findings uggestst hat the specific orientation face of the copper substrate can drive the reactivity of graphene. Furthermore,i ti sa dvantageous to probe the reactivity of graphene directly on copperb ecause one can exclude contamination effects (doping, strain)i nduced by the transfer procedure.…”
Section: Introductionmentioning
confidence: 84%
“…Doping graphene with nitrogen makes the Fermi level of graphene shift upwards, enlarging the difference between graphene and Cu work functions. A strong electrostatic interaction induced by the charge transfer process is expected to be present between the graphene and Cu substrate 15 , 34 , and the resultant electronic coupling at the interface could help to elevate heat dissipation efficiency 15 , 30 , 35 . In addition, the surface orientation of Cu crystallites might affect the interfacial interaction 34 .…”
Section: Discussionmentioning
confidence: 99%
“…A strong electrostatic interaction induced by the charge transfer process is expected to be present between the graphene and Cu substrate 15 , 34 , and the resultant electronic coupling at the interface could help to elevate heat dissipation efficiency 15 , 30 , 35 . In addition, the surface orientation of Cu crystallites might affect the interfacial interaction 34 . Based on the literature study, we deduced that the well bonded NGS-Cu interface is expected to be beneficial for thermal and electrical conductance enhancement in the NGS-Cu nanocomposite.…”
Section: Discussionmentioning
confidence: 99%